2003
DOI: 10.1002/adfm.200304335
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of New ZnO‐Based Phosphors Using a Combinatorial Method

Abstract: The combinatorial method, which was exclusively employed for the drug discovery until recently, has invaded the field of inorganic materials and is becoming a key technology in materials science today. Phosphors, with their diversity of possible mechanisms of luminescence, represent a typical example of a field where the combinatorial approach promises to be especially fruitful. Here, we present the results of systematic combinatorial exploration of different binary and ternary ZnO:dopant systems, which result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 19 publications
1
49
0
1
Order By: Relevance
“…[274] New ZnO-based phosphors have been discovered and optimized by using combinatorial methods to fabricate libraries of thin films by PLD on sapphire or Pt-coated silicon wafers as substrates. [275] ZnO has been doped with the elements (Y,Eu), V, W, (W,Mg) in such amounts that it has to be assumed that almost every ternary or quarternary compound of the phase diagrams is observed as a mixture with other phases in the phosphors despite the fact that, for example, X-ray diffraction experiments did not allow a positive identification of particular vanadate phases because of the low crystallinity of the samples. The authors found that the new phosphors had high low-voltage cathodoluminescence efficiency that potentially will allow their use in flatpanel display and lighting applications.…”
Section: Combinatorial Materials Researchmentioning
confidence: 99%
“…[274] New ZnO-based phosphors have been discovered and optimized by using combinatorial methods to fabricate libraries of thin films by PLD on sapphire or Pt-coated silicon wafers as substrates. [275] ZnO has been doped with the elements (Y,Eu), V, W, (W,Mg) in such amounts that it has to be assumed that almost every ternary or quarternary compound of the phase diagrams is observed as a mixture with other phases in the phosphors despite the fact that, for example, X-ray diffraction experiments did not allow a positive identification of particular vanadate phases because of the low crystallinity of the samples. The authors found that the new phosphors had high low-voltage cathodoluminescence efficiency that potentially will allow their use in flatpanel display and lighting applications.…”
Section: Combinatorial Materials Researchmentioning
confidence: 99%
“…This work led to the discovery of a new RE phosphor, Sr 2 CeO 4 , containing one-dimensional chains of CeO 6 octahedra in their crystal structure. A more recent combinatorial experiment on ZnO-based phosphors 184 involved lattice engineering via precise, unit cell deposition enabled by automated mask motion. The unit cell engineered deposition method results in an extremely well controlled library, and as a result, luminescent behavior can be attributed to precise positions on the library.…”
Section: -23mentioning
confidence: 99%
“…[274] Neue ZnOPhosphore wurden mithilfe kombinatorischer Methoden zur Herstellung von Dünnfilm-Bibliotheken durch PLD auf Saphir oder auf Pt-beschichteten Silicium-Wafern als Substraten entdeckt und optimiert. [275] ZnO wurde dabei mit den Elementen (Y,Eu), V, W, (W,Mg) in solchen Gehalten dotiert, dass angenommen werden kann, dass nahezu jede ternäre wie auch quaternäre Verbindung der Phasendiagramme als Mischung mit anderen Phasen in den resultierenden Materialien vorliegt, trotz der Tatsache, dass Röntgenbeugungsuntersu-chungen keine positive Identifizierung z. B. der jeweiligen Vanadatphasen ergaben, da die Kristallinität der Proben zu gering war.…”
Section: Kombinatorische Materialforschungunclassified